Effect of galium arsenide diode laser on human periodontal disease: Aa microbiological and clinical study - KADİR, TANJU (WILEY, 2002)
Background and Objective: The present study is aimed to describe short-term results on selected microbiological and clinical parameters obtained by treatment with soft laser in conjunction with methylene blue and/or mechanical subgingival debridement in human periodontal disease. Study Design/Materials and Methods: Ten patients, in whom each dental quadrant was randomly designated to receive one of four types of treatment procedures, were included in the study. Groups of quadrants received: scaling/root planing (SRP); laser application (L); SRP combined with L (SRP/L); oral hygiene instructions (OHI). Four single rooted teeth (one in each quadrant), having an interproximal site with a probing depth of 4 mm mesio-buccally, were selected in each patient. The selected teeth were first assessed for microbiological (one site/tooth) and then for clinical variables (six sites/tooth). Supragingival irrigation with methylene blue was performed prior to laser application. The microbiological (proportions of obligate anaerobes) and clinical measurements (plaque and gingival indices, bleeding on probing, probing pocket depth) were evaluated over a period of 32 days. Results: Only the SRP/L and SRP groups provided significant reductions in the proportions of obligate anaerobes before and after treatments with no significant differences in between. Parallel to the microbiological changes, both SRP/L and SRP resulted in similar clinical improvements, whereas L alone revealed a limited effect similar to OHI. Conclusion: Within the limits of this study, methylene blue/soft laser therapy provided no additional microbiological and clinical benefits over conventional mechanical debridement. (C) 2002 Wiley-Liss, Inc.
Keywords: anaerob micro-organisms; mechanical periodontal therapy; soft laser; LOW-POWER LASER; LETHAL PHOTOSENSITIZATION; PORPHYROMONAS-GINGIVALIS; SUBGINGIVAL PLAQUE; ORAL BACTERIA; IN-VITRO; THERAPY; SENSITIZATION; IRRIGATION; POCKETS